2019
DOI: 10.1186/s12889-019-6408-y
|View full text |Cite
|
Sign up to set email alerts
|

To what extent can the activities of the South Australian Health in All Policies initiative be linked to population health outcomes using a program theory-based evaluation?

Abstract: BackgroundThis paper reports on a five-year study using a theory-based program logic evaluation, and supporting survey and interview data to examine the extent to which the activites of the South Australian Health in All Policies initiative can be linked to population health outcomes.MethodsMixed-methods data were collected between 2012 and 2016 in South Australia (144 semi-structured key informant interviews; two electronic surveys of public servants in 2013 (n = 435) and 2015 (n = 483); analysis of state gov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 27 publications
0
51
0
Order By: Relevance
“…An increasing number of public health, and to a lesser extent human rights, scholars are adopting a CR position [e.g] [9, 22–25]. There is also now a large body work in the area of realist evaluation which is informed by a critical realist research paradigm [26], including examples in this journal [e.g] [2729].…”
Section: Critical Realism Research Paradigm – Key Features and Relevamentioning
confidence: 99%
“…An increasing number of public health, and to a lesser extent human rights, scholars are adopting a CR position [e.g] [9, 22–25]. There is also now a large body work in the area of realist evaluation which is informed by a critical realist research paradigm [26], including examples in this journal [e.g] [2729].…”
Section: Critical Realism Research Paradigm – Key Features and Relevamentioning
confidence: 99%
“…For an overview of all findings, and of papers published to report on other themes from the broader project, see Baum et al. ().…”
Section: Methodsmentioning
confidence: 99%
“…Many other themes also emerged from the data at this point, including other interpersonal, structural and governance related facilitators and barriers of HiAP implementation, multiple factors that supported the dissemination of ideas about healthy public policy across SA Government, and understandings about how the broader context surrounding HiAP implementation supported and constrained its impact. For an overview of all findings, and of papers published to report on other themes from the broader project, see Baum et al (2019).…”
Section: Analysis Of Interview Transcriptsmentioning
confidence: 99%
“…In South Australia, for example, the HiAP initiative between government departments aims to find win-win solutions to problems and to establish relationships built upon trust and which can use co-benefit approaches [ 17 ]. The evaluation of the project using a narrative theory of change indicated that its varied initiatives did, in all probability, lead to health gains [ 18 ].…”
Section: Health In All Policies: Governing For Health Equity and mentioning
confidence: 99%
“…In one city, for example, the urban planning and health departments identified shared goals related to bicycle infrastructure. The planning department’s goal to create a “vibrant” city converged with the health department’s goal of encouraging cycling for health benefits [ 18 ]. The HiAP initiative contributed to ensuring that the 30 year plan for the city contained multiple initiatives designed to promote health including increased walkability, improved public transport, and more livable suburbs [ 19 ].…”
Section: Health In All Policies: Governing For Health Equity and mentioning
confidence: 99%